FAKTOR YANG MEMPENGARUHI PENCIPTAAN BUDGETARY SLACK (Studi Empiris pada SKPD Kota Surakarta) - Denisse Sunarchrisna; Kun Ismawati (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2017)
This study aims to analyze the inï¬‚uence of obedience pressure factors, budget participation and perceptions of responsibility have an inï¬‚uence on the creation of budgetary slack. Based on the results of this study can give thought and consideration in determining the policy of obedience pressure, budget participation and perceptive responsibility factors so as to minimize the occurrence of budget slack. Hypothesis testing in this study using multiple regression analysis tools with t test and F test. Population in this research is all employees of Organization of Regional Device (OPD) Surakarta. Sampling method used in this study is purposive sampling based on the criteria that have been described above, then obtained 25 OPD as a sample with the number of 52 employees. Based on the results of the research note that the pressure of obedience has a signifcant negative effect on budgetary slack on the Organization of the Regional Area of Surakarta City, so H1 accepted. Budget participation has a signifcant positive effect on the budgetary slack on the Organization of the Regional Area of Surakarta City so that H2 is accepted. Responsibility of perception has a signifcant positive effect on the budgetary slack on the Organization of Local Area of Surakarta City so that H3 is accepted